THU0460 Clinical Characteristics and the Course after Corticosteroid Therapy in IgG4-Related Aortitis/Periaortitis and Periarteritis. (23rd January 2014) - Mizushima, I.; Inoue, D.; Yamada, K.; Saeki, T.; Ubara, Y.; Suzuki, Y.; Fujii, H.; Matsumura, M.; Yamagishi, M.; Notohara, K.; Kawano, M.
Abstract : Background: Recently, the new concept of IgG4-related disease (IgG4-RD) has been proposed [1 ], and it has been revealed that some chronic aortitis/periaortitis patients have an IgG4-related condition according to past studies examining surgically treated cases [2 ]. However, clinical characteristics and the course after corticosteroid (CS) therapy in patients with IgG4-related aortitis/periaortitis and periarteritis have not been well clarified. Objectives: To clarify the clinical characteristics and the course after CS therapy in IgG4-related aortitis/periaortitis and periarteritis Methods: We retrospectively evaluated clinical features including laboratory data, imaging findings and the clinical course after CS therapy in 20 patients diagnosed as having IgG4-related aortitis/periaortitis and periarteritis based on serum IgG4 levels, radiographic findings surrounding the artery, and extra-vascular IgG4-related organ involvement. Results: Seventeen patients were men, and three were women (average age 66.3 years). Average follow-up period was 29.2 months (range 1-120 months). At diagnosis, their serum IgG4 concentration was 675 ± 541 mg/dL. Eighteen patients had extra-vascular organ involvement that fulfilled the diagnostic criteria of IgG4-RD [3 ]. Average number of organs involved was 3.7, with the most frequently affected organs being salivary glands (60%) and pancreas (40%). Concerning subjective signs/symptoms, only one patient showed low-grade fever, and no one complained of pain. The affected aorta/artery comprised 18 abdominal aortas, 4 thoracic aortas, 13 iliac arteries, one femoral artery, and two mesenteric arteries. Sixteen patients were treated with prednisolone (PSL) at an average initial dose of 29.3 mg/day (range 20-45 mg/day), and reduction in the size of the perivascular lesions was observed in 15 patients after therapy, although one patient showed relapse during PSL tapering at a dose of 7 mg/day. Five of 20 patients (25%) had aneurysm or slight lumen enlargement of the affected lesions at diagnosis. One of them was treated surgically. The other four patients were treated with PSL, in two (50%) of whom the aneurysm enlarged during the follow-up. New aneurysm formation was not observed in patients who had not had aneurysm of the affected lesions at diagnosis. Conclusions: In the present study, clinical characteristics such as scanty subjective symptoms and much other organ involvement were identified in IgG4-related aortitis/periaortitis and periarteritis. Although the response to CS was good, some patients who had had aneurysm or slight lumen enlargement of the affected lesions at diagnosis showed aneurysm enlargement after CS therapy. These results suggest the necessity of systemic evaluation through radiographic examination not only at diagnosis but also during and after CS therapy in IgG4-RD. References: Stone JH et al. IgG4-related disease.N Engl J Med. 2012;366(6):539-51. Kasashima S et al. IgG4-related inflammatory abdominal aortic aneurysm. Curr Opin Rheumatol. 2011;23(1):18-23. Umehara H et al. Comprehensive diagnostic criteria for IgG4-related disease (IgG4-RD), 2011. Mod Rheumatol. 2012;22(1):21-30. Disclosure of Interest: None Declared